Guideline clinical nutrition in patients with stroke - Wirth, Rainer (BioMed Central, 2013)
Stroke is regularly accompanied by dysphagia and other factors associated with decreased nutritional intake. Dysphagia with aspiration pneumonia and insufficient nutritional intake lead to worse outcome after stroke. This guideline is the first chapter of the guideline “Clinical Nutrition in Neurology” of the German Society for Clinical Nutrition (DGEM) which itself is one part of a comprehensive guideline about all areas of Clinical Nutrition. The thirty-one recommendations of the guideline are based on a systematic literature search and review, last updated December 31, 2011. All recommendations were discussed and consented at several consensus conferences with the entire DGEM guideline group. The recommendations underline the importance of an early screening and assessment of dysphagia and give advice for an evidence based and comprehensive nutritional management to avoid aspiration, malnutrition and dehydration.